I must say my life as a humble comedy legend - Short, Martin 1945- (HarperCollins, 2014)
The Emmy Award and Tony Award-winning actor and comic shares stories from his life that recount his early years with Saturday Night Live, the development of his numerous characters, his family life and his celebrity friendships